(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the role of information in the globalization of the economy, the introduction of information-communication and computer technologies and their rapid development, bringing great changes to our society, the formation of a common information society in the world, the importance of information in the economic sphere , it was analyzed that ensuring fast and high-quality circulation of information becomes a key criterion for the development and prosperity of the country.